Use of controlled release organic mineral fertilizer in soybean crop - Robson Thiago Xavier de Sousa; Bruna Couto Molinar Henrique; Leonardo Couto Molinar Henrique; Humberto Henrique (The Journal of Engineering and Exact Sciences)
This work aims to investigate the efficiency of a novel organic mineral fertilizer produced with filter cake residue from sugarcane mills. The novel fertilizer was developed based on the mixing of minerals with an organic compost, conditioning, and pelletizing of mixture. The minerals consist of conventional soluble mineral nutrients and the organic phase consists of insoluble filter cake compost obtained from an assisted composting process. Efficiency of conventional and organic mineral fertilizers was measured in real field soybean crop through a randomized block design with four replications. Variables analyzed were productivity, NPK nutrient in leaves. The experiment was carried out in Tupaciguara/MG, Brazil. Experimental results showed higher soybean productivity and leaf nitrogen content in the organic mineral treatments than mineral ones in all dosages tested, with statistical relevance for 80% and 100% NPK dosages.